Ultrastructural Analysis of Chikungunya Virus Dissemination from the Midgut of the Yellow Fever Mosquito, Aedes aegypti - Asher M. Kantor; DeAna G. Grant; Velmurugan Balaraman; Tommi A. White; Alexander W. E. Franz (Viruses, 2018)
The transmission cycle of chikungunya virus (CHIKV) requires that mosquito vectors get persistently infected with the virus, following its oral acqsuisition from a vertebrate host. The mosquito midgut is the initial organ that gets infected with orally acquired CHIKV. Following its replication in the midgut epithelium, the virus exits the midgut and infects secondary tissues including the salivary glands before being transmitted to another host. Here, we investigate the pattern of CHIKV dissemination from the midgut of Aedes aegypti at the ultrastructural level. Bloodmeal ingestion caused overstretching of the midgut basal lamina (BL), which was disrupted in areas adjacent to muscles surrounding the midgut as shown by scanning electron microscopy (SEM). Using both transmission electron microscopy (TEM) and focused ion beam scanning electron microscopy (FIB-SEM) to analyze midgut preparations, mature chikungunya (CHIK) virions were found accumulating at the BL and within strands of the BL at 24–32 h post-infectious bloodmeal (pibm). From 48 h pibm onwards, virions no longer congregated at the BL and became dispersed throughout the basal labyrinth of the epithelial cells. Ingestion of a subsequent, non-infectious bloodmeal caused mature virions to congregate again at the midgut BL. Our study suggests that CHIKV needs a single replication cycle in the midgut epithelium before mature virions directly traverse the midgut BL during a relatively narrow time window, within 48 h pibm.